2017
DOI: 10.1186/s10397-017-1000-x
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic uterovaginal prolapse surgery in the elderly: feasibility and outcomes

Abstract: BackgroundUterovaginal prolapse in very elderly women is a growing problem due to increased life expectancy. Surgeons and anaesthetists may be wary of performing quality of life surgery on this higher risk group. Where surgery is undertaken, it is commonly performed vaginally; there is a perception that this is better tolerated than abdominal surgery.Little data is published about laparoscopic prolapse surgery tolerability in this population, and laparoscopic surgery is perceived within the urogynaecological c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Our findings concur with those of Boudy et al [27] who analyzed 47 women aged 70 or more, who constituted 24.6 % of their study participants, and found comparable low frequencies of perioperative complications [27]. In view of the retrospective nature of the studies that have reported on LSC outcomes in different age groups and the lack of availability of the total number of women who presented with a significant a-POP during the studied periods we were not able to calculate their actual feasibility rates for undertaking this procedure in older age, and hence higher operative risk, groups [27,27,28,29]. In contrast, in our study LSC was offered to 85.5 % of the women with a preoperative ASA-PS!3.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Our findings concur with those of Boudy et al [27] who analyzed 47 women aged 70 or more, who constituted 24.6 % of their study participants, and found comparable low frequencies of perioperative complications [27]. In view of the retrospective nature of the studies that have reported on LSC outcomes in different age groups and the lack of availability of the total number of women who presented with a significant a-POP during the studied periods we were not able to calculate their actual feasibility rates for undertaking this procedure in older age, and hence higher operative risk, groups [27,27,28,29]. In contrast, in our study LSC was offered to 85.5 % of the women with a preoperative ASA-PS!3.…”
Section: Discussionmentioning
confidence: 92%
“…We did not identify other studies that have assessed LSC outcomes in relation to ASA-PS scores to compare our results to. Nevertheless, there are several studies that assessed LSC operative outcomes in relation to women's age [26][27][28][29]. In a study by Turner and colleagues where participants had a mean age of 58.5 years, they reported higher perioperative complication rates amongst women who were !65 years at the time of the procedure [26].…”
Section: Discussionmentioning
confidence: 99%